2019
DOI: 10.1111/odi.13220
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the HADS and PSS‐10 and psychological status in patients with oral lichen planus

Abstract: Objectives: To validate the Hospital Anxiety and Depression Scale (HADS) and the 10-item Perceived Stress Scale (PSS-10) for use in patients with oral lichen planus (OLP) and to provide cross-sectional analysis of anxiety, depressive and distress symptoms in patients with OLP.Methods: Validity and reliability of both instruments were assessed in 260 participants with OLP in one tertiary Oral Medicine Centre through confirmatory factor analysis and calculation of reliability coefficients. Prevalence, Clinical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 54 publications
4
23
1
Order By: Relevance
“…A significantly higher number of non-alcohol drinkers with RAS in this study have depressive symptoms when compared to those who consume alcohol. This finding matched several studies in different conditions including oral lichen planus, 28 which found the increased risk of having depressive symptoms among non-alcohol drinkers. One possible explanation of this association might be a result of certain social confounding factors.…”
Section: Discussionsupporting
confidence: 91%
“…A significantly higher number of non-alcohol drinkers with RAS in this study have depressive symptoms when compared to those who consume alcohol. This finding matched several studies in different conditions including oral lichen planus, 28 which found the increased risk of having depressive symptoms among non-alcohol drinkers. One possible explanation of this association might be a result of certain social confounding factors.…”
Section: Discussionsupporting
confidence: 91%
“…One third of patients with OLP have psychological comorbidities like anxiety, depressive or distress symptoms [ 33 35 ]. It is believed that autoimmune diseases influence the psyche of affected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression are common cofactors in OLP [ 25 ]. In a study by Wiriyakijja et al, prevalences of anxiety, depression and distress were 39.23%, 20.77% and 27.69%, respectively [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Signs of anxiety, depression and distress were examined in a study by Wiriyakijja et al One-third of 260 patients named psychological complaints. Patients with these mental concomitant diseases had significantly more frequent physical pain in the mouth area than patients without concomitant diseases [ 26 ]. As already known for other chronic diseases, somatic complaints have an impact on the psyche [ 29 ].…”
Section: Discussionmentioning
confidence: 99%